Chalcone derivatives as promising antifoulants: Molecular optimization, bioactivity evaluation and performance in coatings - Daniela Pereira; Andreia Palmeira; Érica Lima; Vitor Vasconcelos; Madalena Pinto; Marta Correia-da-Silva; Joana R. Almeida; Honorina Cidade (Ecotoxicology and Environmental Safety, 2024)
Marine biofouling remains a huge concern for maritime industries and for environmental health. Although the current biocide-based antifouling coatings can prevent marine biofouling, their use has been associated with toxicity for the marine environment, being urgent to find sustainable alternatives. Previously, our research group has identified a prenylated chalcone (1) with promising antifouling activity against the settlement of larvae of the macrofouling species Mytilus galloprovincialis (EC50 = 16.48 µM and LC50 > 200 µM) and lower ecotoxicity when compared to Econea®, a commercial antifouling agent in use. Herein, a series of chalcone 1 analogues were designed and synthesized in order to obtain optimized antifouling compounds with improved potency while maintaining low ecotoxicity. Compounds 8, 15, 24, and 27 showed promising antifouling activity against the settlement of M. galloprovincialis larvae, being dihydrochalcone 27 the most potent. The effect of compound 24 was associated with the inhibition of acetylcholinesterase activity. Among the synthesized compounds, compound 24 also showed potent complementary activity against Navicula sp. (EC50 = 4.86 µM), similarly to the lead chalcone 1 (EC50 = 6.75 µM). Regarding the structure-activity relationship, the overall results demonstrate that the substitution of the chalcone of the lead compound 1 by a dihydrochalcone scaffold resulted in an optimized potency against the settlement of mussel larvae. Marine polyurethane (PU)-based coatings containing the best performed compound concerning anti-settlement activity (dihydrochalcone 27) were prepared, and mussel larvae adherence was reduced compared to control PU coatings.